بعض المشكلات السلوكية السائدة لدى أطفال ذوي اضطراب طيف التوحد - ميدون, مباركة; خلادي, يمينة (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة الحالية إلى التحقق من الأهداف المتمثلة في الكشف عن المشكلات السلوكية لدى أطفال ذوي اضطراب طيف التوحد بمراكز مدينة ورقلة، وفي ما إذا كانت هناك فروق في تلك المشكلات تبعا لمتغير جنس الطفل. اعتمدت الدراسة على المنهج الوصفي الاستطلاعي المقارن، وقد تكونت عينة الدراسة من (23) طفل ذوي اضطراب طيف التوحد متواجدين بالمراكز الخاصة في مدينة ورقلة، تم اختيارهم بطريقة عرضية(الصدفة)، وللإجابة على تساؤلات الدراسة تم تطبيق مقياس كارز2 لتشخيص اضطراب طيف التوحد ، وبطاقة الملاحظة للمشكلات السلوكية للأطفال ذوي اضطراب طيف التوحد (من إعداد الباحثتين )، بعد تقدير بعض خصائصه السيكومترية والمتمثلة في الصدق والثبات. وقد أسفرت النتائج على أن: مشكلة السلوكات النمطية كان السلوك الأكثر انتشارا لدى الأطفال ذوي اضطراب طيف التوحد تليه السلوكيات العدوانية وأخيرا سلوكيات إيذاء الذات ، وأظهرت النتائج أيضا وجود فروق ذات دلالة إحصائية بين متوسطي درجات الأطفال الذكور والإناث في المشكلات السلوكية ولصالح الذكور .ABSTRACT:The current study aimed to verify behavioral problems targets detected at children with autism spectrum disorder at Ouargla town centers, if there are differences in these problems depending to variable child gender, this study based on exploratory descriptive method. The sample of study is consisted of 23 children with autism spectrum disorder present in special centers in the city of Ouargla town, were selected accident(chance).to answer to the study questions, it has been applied(cars-2) scale to diagnostic for autism spectrum disorder, and observation card for children behavioral problems with autism spectrum disorder (prepared by the researcher), after assessment some psychometric characteristics of validity and reliability. The results showed that the stereotypical behavior problem was the most behavior prevalent at children with autism spectrum disorder followed by aggressive behaviors and self-harming behaviors, also showed that there are differences of statistic significant between males and females finally grades in behavior problems for males.
مقال
Keywords: المشكلات السلوكية؛ أطفال اضطراب طيف التوحد; behavioral problems; children with autism spectrum disorder